Design and Political Artifacts - Winner, Langdon (My University, 2017)
A reflection on Design and Political Artifacts by Thomas Phelan Chair at Rensselaer Polytechnic Institute Langdon Winner.
Diseño y Artefactos políticos
Diseño y artefactos políticos
A reflection on Design and Political Artifacts by Thomas Phelan Chair at Rensselaer Polytechnic Institute Langdon Winner.
Keywords: Diseño; Accesibilidad para minusválidos; Artefactos políticos; Filosofia de la tecnología; Arquitectura